2020
DOI: 10.3390/agronomy10070976
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Soil Tillage and Nitrogen Rate to the Quality of Maize Grain

Abstract: A soil tillage system adjusted to the soil type and agro-ecological conditions, together with the optimal nutrient supply, is a prerequisite for high maize (Zea mays L.) yield. However, there is little knowledge about the influence of soil tillage and nitrogen (N) rates on maize grain quality. A study was initiated in 1978 in Zemun Polje, Belgrade, Serbia, on the chernozem soil type. The effects of three N rates—0, 180 and 240 kg N ha−1—within three tillage practices—no-tillage, reduced and conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
4
17
0
2
Order By: Relevance
“…On the contrary, Asami et al [34] noted that management practices affected TPC of wheat. Simić et al, 2020 [35] tried to test the effect of tillage and cultivation year on maize and found that, phenolic content showed significant variations according to tillage system and growing season.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…On the contrary, Asami et al [34] noted that management practices affected TPC of wheat. Simić et al, 2020 [35] tried to test the effect of tillage and cultivation year on maize and found that, phenolic content showed significant variations according to tillage system and growing season.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…One of the main principles of today's agriculture is the use of crop-growing systems including optimal agronomic practices to ensure the efficient use of all inputs for crop productivity and economic profitability while maintaining the quality of the environment and the sustainability of the agroecosystem [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis models are particularly useful for identifying patterns when data from multiple sources are combined and analyzed [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Thus, for the comparison of water stress and N fertilization effects on grain quality components, random effects meta-analysis models were fit following the log response ratio (lnRR) approach [42].…”
Section: Meta-analysismentioning
confidence: 99%